2001
DOI: 10.1046/j.0014-2956.2001.02600.x
|View full text |Cite
|
Sign up to set email alerts
|

A putative β2‐adrenoceptor from the rainbow trout (Oncorhynuchus mykiss)

Abstract: Extensive molecular characterization of mammalian b-adrenoceptors has revealed complex modes of regulation and interaction. Relatively little attention, however, has focused on adrenoceptors from early branching vertebrates such as fish. Using an RT-PCR approach we have cloned a rainbow trout b 2 -adrenoceptor gene that codes for a 409-amino-acid protein with the same seven transmembrane domain structure as its mammalian counterparts. This rainbow trout b 2 -adrenoceptor shares a high degree of amino-acid sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Within the most commonly used �-blockers propranolol is a non-specific antagonist, blocking both �1 and �2-receptors while metoprolol and atenolol present �1-receptors specificity [99]. Fish, like other vertebrates, possess �-receptors in the heart, liver and reproductive system [170,171] so that pro-longed exposure to drugs belonging to this therapeutic class may cause deleterious effects. From a two weeks study, it was observed that exposure to 500 µg L −1 of propranolol reduced growth rates of Japanese medaka [172].…”
Section: Beta-blockersmentioning
confidence: 99%
“…Within the most commonly used �-blockers propranolol is a non-specific antagonist, blocking both �1 and �2-receptors while metoprolol and atenolol present �1-receptors specificity [99]. Fish, like other vertebrates, possess �-receptors in the heart, liver and reproductive system [170,171] so that pro-longed exposure to drugs belonging to this therapeutic class may cause deleterious effects. From a two weeks study, it was observed that exposure to 500 µg L −1 of propranolol reduced growth rates of Japanese medaka [172].…”
Section: Beta-blockersmentioning
confidence: 99%
“…Xiao et al, 1999;Bernstein, 2002). This dual coupling of 2AR might help explain why this receptor is not involved to the same extent as 1AR in G s -mediated cAMPexpression of ARs in the fish heart, and that fish hearts are responsive to classic AR ligands (Nickerson et al, 2001;Kawasaki et al, 2008;Mendonça and Gamperl, 2009;Steele et al, 2009). Some studies on fish ARs have also shown that they can have unexpected affinity for (presumed) subtype-specific agonists.…”
Section: Introductionmentioning
confidence: 99%
“…As β-adrenergic receptors are also present in heart, hepatocytes and reproductive tissues of fish and other vertebrates, it is possible that these organisms can also be affected by β-blockers action (Nickerson et al, 2001). …”
Section: Propranololmentioning
confidence: 99%